Development and root morphology of passion fruit in different substrates - Valle, Karminne Dias Do; Pereira, Laísse Danielle; Barbosa, Moab Acácio; Chaves, Vanessa Brenda Souza; Souza, Pedro Henrique Magalhães de; Reis, Edésio Fialho Dos; Hurtado Salazar, Alejandro; Pereira Da Silva, Danielle Fabiola (Universidad Pedagógica y Tecnológica de Colombia, 2019)
1 recurso en línea (páginas 514-520).